Comparison of clinical characteristics, eating behaviors, and clinical symptoms following fat intake in functional dyspepsia with functional dyspepsia with pancreatic enzyme abnormalities between Singapore and Japan. Issue 8 (11th May 2022) - Futagami, Seiji; Kessoku, Takaomi; Kasai, Yuki; Higurashi, Takuma; Nakajima, Atsushi; Agawa, Shuhei; Yamawaki, Hiroshi; Habiro, Mayu; Ueki, Nobue; Sanada, Iori; Yamamoto, Mariko; Watanabe, Yoshiyuki; et al.
Abstract: Background and Aim: To clarify whether there were any significant differences in clinical symptoms and eating patterns between functional dyspepsia (FD) patients and FD with pancreatic enzyme abnormalities (FD‐P) patients as refractory FD, we compared these factors in multicenter studies in Singapore and Japan. Methods: One hundred ninety‐eight consecutive patients presenting with FD ( n = 88), FD‐P patients ( n = 81) based on Rome III classification and controlled group ( n = 39) recruited from six institutions in Singapore and Japan. Clinical characteristics, clinical symptoms for dietary fat intake, and eating behaviors were estimated using questionnaires. Anxiety and health‐related quality of life were determined by STAI‐state/‐trait and SF‐8, respectively. Results: There were no significant differences in age, sex, BMI, smoking, alcohol intake, past medical history, and history of allergy in FD and FD‐P patients between Singapore and Japan. There were no significant differences in FD subtypes, gastrointestinal symptom rating scale score, severity of FD symptoms, and eating pattern in Singapore and Japan. Moreover, there were significant differences in certain eating behaviors between FD and FD‐P patients in Singapore and Japan. Interestingly, epigastric pain and early satiety following fat meals in FD‐P patients were significantly ( P = 0.003 and P = 0.008, respectively) higher compared with those in FD patients in Japan. Physical component score in FD‐P patients was significantly ( P = 0.019) disturbed compared with those in FD patients in Japan. Conclusions: Epigastric pain and early satiety following fat meals in FD‐P patients may be useful tools to differentiate FD‐P patients from FD patients in Japan.